Marine Bivalve Mollusks As Possible Indicators of Multidrug-Resistant Escherichia coli and Other Species of the Enterobacteriaceae Family - Grevskott, Didrik H.; Svanevik, Cecilie S.; Sunde, Marianne; Wester, Astrid L.; Lunestad, Bjørn T. (Frontiers in Microbiology, 2017)
The mechanisms for the development and spread of Antibacterial Resistance (ABR) in bacteria residing in environmental compartments, including the marine environment, are far from understood. The objective of this study was to examine the ABR rates in Escherichia coli and other Enterobacteriaceae isolates obtained from marine bivalve mollusks collected along the Norwegian coast during a period from October 2014 to November 2015. A total of 549 bivalve samples were examined by a five times three tube Most Probable Number method for enumeration of E. coli in bivalves resulting in 199 isolates from the positive samples. These isolates were identified by biochemical reactions and Matrix Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry, showing that 90% were E. coli, while the remaining were species within the genera Klebsiella, Citrobacter, and Enterobacter. All 199 isolates recovered were susceptibility tested following the European Committee on Antimicrobial Susceptibility Testing (EUCAST) disk diffusion method. In total, 75 of 199 (38%) isolates showed resistance to at least one antibacterial agent, while multidrug-resistance were seen in 9 (5%) isolates. One isolate conferred resistance towards 15 antibacterial agents. Among the 75 resistant isolates, resistance towards extended-spectrum penicillins (83%), aminoglycosides (16%), trimethoprim (13%), sulfonamides (11%), tetracyclines (8%), third-generation cephalosporins (7%), amphenicols (5%), nitrofurans (5%), and quinolones (5%), were observed. Whole-genome sequencing on a selection of ten E. coli isolates identified the genes responsible for resistance, including blaCTX-M genes. To indicate the potential for horizontal gene transfer, conjugation experiments were performed on the same selected isolates. Conjugative transfer of resistance was observed for six of the ten E. coli isolates. In order to compare E. coli isolates from bivalves with clinical strains, Multiple-Locus Variable Number Tandem Repeats Analysis (MLVA) was applied on a selection of 30 resistant E. coli isolates. The MLVA-profiles were associated with community-acquired E. coli strains causing bacteremia. Our study indicates that bivalves represent an important tool for monitoring antibacterial resistant E. coli and other members of the Enterobacteriaceae family in the coastal environment.